Pengembangan Bank Sampah Melalui Pemanfaatan Teknologi Trash Burner Untuk Meningkatan Kesehatan Masyarakat Dan Lingkungan Desa - Sri Hilmi Pujihartati; Adryan Adryan; Ika Purnama Wati (Jurnal Pengabdian Pada Masyarakat, 2022)
DEVELOPING WASTE BANK THROUGH UTILIZATION OF TRASH BURNER TECHNOLOGY TO IMPROVE COMMUNITY HEALTH AND ENVIRONMENT. KKN is a student learning process through the implementation of various activities directly in the community. Students as agents of change carry an important role for society. Student study service (KKN) are one of the real manifestations of college student service to the community through assistance in training counseling, mentoring, empowerment, and to increase the awareness of the community in order to improve the quality of a healthy environment. One of the problems that exist in the community of Jimus Village, Polanharjo District, Klaten is the lack of public awareness and knowledge in processing household waste. The work program chosen by KKN students is the development of a waste bank owned by Jimus village. The development activities carried out by students include cleaning several landfills, providing innovations in waste processing, to providing technological innovations to process waste. Thus, after the UNS KKN activity ends, it is hoped that the Jimus village community will have a high awareness of the impact of littering and be able to process household waste better to improve the quality of a healthier living environment.